2012
DOI: 10.1152/ajprenal.00596.2011
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil as a novel therapy for advanced diabetic nephropathy in the eNOS-deficient mouse

Abstract: Nicorandil is an orally available drug that can act as a nitric oxide donor, an antioxidant, and an ATP-dependent K channel activator. We hypothesized that it may have a beneficial role in treating diabetic nephropathy. We administered nicorandil to a model of advanced diabetic nephropathy (the streptozotocin-induced diabetes in mice lacking endothelial nitric oxide synthase, eNOSKO); controls included diabetic eNOS KO mice without nicorandil and nondiabetic eNOS KO mice treated with either nicorandil or vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
3
38
0
Order By: Relevance
“…This finding is consistent with the prior experimental studies (17,19), as well as a recent report that nicorandil could reduce proteinuria in hypertensive subjects (8). Our laboratory has recently reported that nicorandil potently reduced urinary albumin excretion in diabetic endothelial NO synthase-deficient mice (20). In that study, our laboratory showed that nicorandil protects podocytes from high-glucose-induced oxidative stress by activating K ATP channels.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the prior experimental studies (17,19), as well as a recent report that nicorandil could reduce proteinuria in hypertensive subjects (8). Our laboratory has recently reported that nicorandil potently reduced urinary albumin excretion in diabetic endothelial NO synthase-deficient mice (20). In that study, our laboratory showed that nicorandil protects podocytes from high-glucose-induced oxidative stress by activating K ATP channels.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetic nephropathy was induced by intraperitoneal injections of streptozotocin (50 mg/kg per day for 5 consecutive days) dissolved in 10 mM citrate buffer, pH 4.5. 39 After streptozotocin administration, 96% of mice became diabetic. Mice were divided into four subgroups (n$6/group): (1) a nondiabetic wild-type group, (2) a nondiabetic khk2/2 group, (3) a diabetic wild-type group, and (4) a diabetic khk2/2 group.…”
Section: Micementioning
confidence: 99%
“…39 The following antibodies were used as primary antibodies: (1) rabbit anti-type IV collagen antibody (Chemicon International, Temecula, CA), (2) rabbit anti-mouse aldose reductase (AKR1B1) antibody (Novus Biologicals, Littleton, CO), (3) rabbit anti-mouse fructokinase (KHK) antibody (for both KHK-A and KHK-C isoforms; Sigma-Aldrich); (4) goat anti-type III collagen antibody (Southern Biotech, Birmingham, AL), and (5) rabbit anti-ACE antibody (Chemicon). Briefly, after deparaffinization, the sections were treated with 3% H 2 O 2 for 10 minutes to inactivate endogenous peroxidase activity.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The renoprotective effect of nicorandil has been reported in several studies. Nicorandil suppresses glomerular injury (mesangiolysis and glomerulosclerosis) not only in anti-Thy1 nephritis rats through the prevention of mesangial proliferation and extracellular matrix production [15] , which was supported by in vitro data showing that nicorandil inhibits mesangial cell proliferation in rats via the protein kinase G pathway [39] , but also in streptozotocin-treated eNOS-knockout diabetic mice through podocyte protection [53] . At present, the precise mechanism of the renoprotective effect is not clear, although originally nicorandil was known as a cardioprotective agent, which enhances cardiac eNOS expression via activation of an ATP-sensitive potassium (K ATP ) channel in rats [54] .…”
Section: Discussionmentioning
confidence: 98%